2015
DOI: 10.1080/23311932.2014.995950
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative effect of gibberellic acid and phosphorus on crop productivity, biochemical activities and trigonelline production in Trigonella foenum-graecum L.

Abstract: Fenugreek (Trigonella foenum-graecum L.) is an antidiabetic plant. Its bioactive compound, trigonelline, is known to counter diabetes through insulin secretion, modulation of β cell regeneration and quick activity of glucose metabolism related enzymes. A pot experiment was conducted in the natural conditions of net house of the Department of Botany, Aligarh Muslim University, Aligarh (UP), India, to evaluate the effect of four concentrations of GA 3 (0, 10 −7 M, 10 −6 M and 10 −5 M), alone and in combination w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
2
5
0
2
Order By: Relevance
“…Among all photosynthetic organisms, the carotenoids act as protecting "antenna pigments" for photosynthesis, gathering wavelengths of light that are not absorbed by chlorophylls (Vichnevetskaia and Roy, 1999). In fact, our results are consistent with previously reported findings that the GA 3 enhanced the carotenoids contents in V. radiata (El Karamany et al, 2019), Artemisia annua (Aftab et al, 2010), rice (Ghodrat et al, 2013), corn (Al-Shaheen et al, 2014), Trigonella foenum-graecum (Ahmad Dar et al, 2015). It is suggested that the increase in carotenoid content by GA 3 may be due to development of ultrastructural morphogenesis of plastids (Arteca, 1996).…”
Section: Photosynthetic Pigmentssupporting
confidence: 92%
See 3 more Smart Citations
“…Among all photosynthetic organisms, the carotenoids act as protecting "antenna pigments" for photosynthesis, gathering wavelengths of light that are not absorbed by chlorophylls (Vichnevetskaia and Roy, 1999). In fact, our results are consistent with previously reported findings that the GA 3 enhanced the carotenoids contents in V. radiata (El Karamany et al, 2019), Artemisia annua (Aftab et al, 2010), rice (Ghodrat et al, 2013), corn (Al-Shaheen et al, 2014), Trigonella foenum-graecum (Ahmad Dar et al, 2015). It is suggested that the increase in carotenoid content by GA 3 may be due to development of ultrastructural morphogenesis of plastids (Arteca, 1996).…”
Section: Photosynthetic Pigmentssupporting
confidence: 92%
“…The root dry weight was always higher in BARI Mung-8 than in BARI Mung-6 in this study. It has been reported that GA 3 increases the root dry weight in beans (Jaques et al, 2019), Trigonella foenumgraecum (Ahmad Dar et al, 2015), the dry weight of pods in French bean (Gabal et al, 1990), and bulbs in onion (Hore et al, 1988). However, exogenous application of GA 3 through seed priming in V. radiata did not influence the root dry weight as reported by Kundu et al (2017), which contradicts in our findings.…”
Section: Root Dry Weightmentioning
confidence: 99%
See 2 more Smart Citations
“…Seed extracts of fenugreek such as galactomannan is used as industrial thickener. According to some recent studies it was revealed that fenugreek can be suggested as a possible remedy for diabetes lowering blood sugar and cholesterol level (AHMAD DAR et al, 2015).…”
Section: Introductionmentioning
confidence: 99%